Evaluation of communication between health professionals and users of a public maternity hospital (Research, Society and Development, 2020)
Objective: To evaluate the perception of health professionals and users about communication in the hospital environment. Methodology: This is a qualitative, exploratory and descriptive field research. To understand the results and the meaning of communication between professionals and users, the data were organized from the speeches of patients and health professionals from a public maternity hospital. Results: Among the 20 users interviewed, 14 (70%) said that communication is great, 01 (5%) people reported that communication is regular, but needs to improve, 03 (15%) people said that communication is more or less and 02 (10%) people reported that communication is poor. Among the 20 professionals interviewed, 05 (25%) said they need not change that their communication with the patient is excellent, 09 (5%) people reported that it is always good to improve their communication with the patient 02 (10%) people spoke that their communication with the user is humanized and 04 (20%) people reported that because of the short time that communication has to be quickly explaining the entire procedure. Conclusion: there are still communication failures, since the professional is more focused on the procedure, forgetting the provision of humanized care. Thus it is expected that there will be more empathy and responsibility with the parties involved for the development of a humanized assistance, understanding the users' complaints and reducing the communication failures.